95-kilodalton B-Raf serine/threonine kinase: identification of the protein and its major autophosphorylation site. - Stephens, R M (1992)
B-Raf, a member of the Raf family of serine/threonine kinases, is expressed primarily in the brain and in the nervous system. In this study, the biochemical properties of the B-Raf protein were investigated in nerve growth factor (NGF)-responsive cell lines and in brain tissues. B-Raf was identified by using phosphopeptide mapping analysis and cDNA analysis as a 95-kDa protein which is primarily localized in the cytosol. NGF rapidly stimulated both serine and threonine phosphorylation in vivo and autophosphorylation activity in vitro of the B-Raf protein. In PC12 cells, B-Raf autokinase activity was induced by both differentiation factors and mitogens, with maximal activity observed after 5 min of factor addition. B-Raf kinase activity was also observed following NGF treatment of SH-SY5Y neuroblastoma cells and in adult mouse brain and hippocampus. Induction of B-Raf kinase activity in NGF-treated PC12 cells required expression of kinase-active trk receptors. Exogenous substrates or a peptide containing the autophosphorylation site became phosphorylated when added to immune complex kinase assays and reduced the in vitro autophosphorylation activity of B-Raf, suggesting that in vitro autophosphorylation sites and exogenous substrates compete for active sites of the B-Raf kinase. Finally, the major in vitro autophosphorylation site of B-Raf was identified as threonine 372 in the conserved region 2 domain. A threonine residue is present at similar positions in all three mammalian Raf family members and may represent a regulatory site for these proteins.